Robotic Surgical Procedures for Ventral Hernia Repair - M. W. Christoffersen; K. Andresen; K. Andresen; Helene Perregaard; N. A. Henriksen; N. A. Henriksen (Journal of Abdominal Wall Surgery)
The recent availability of robotic platforms has facilitated the adoption of advanced minimally invasive ventral hernia repair. Robotic-assisted ventral hernia repair is an evolving field with many new techniques and acronyms for different accesses and approaches. This paper aims to describe the four currently most used procedures for robotic ventral hernia repair, all of which are MIS sublay repairs; robotic Trans-Abdominal-Preperitoneal (r-TAPP), robotic Trans-Abdominal-Retromuscular-Mesh (r-TARM), robotic Extended-Totally-Extra-Peritoneal (r-E-TEP), and robotic Transversus-Abdominis-Release (RoboTAR). Their descriptions are supported by illustrations. The paper describes trocar placement, practical tips and tricks, and briefly discusses the indications for each procedure. Furthermore, technical details such as the incision of the flap, access to the correct anatomical planes, dissection techniques, handling of the hernia sac, mesh choice and placement, and restoration of the abdominal wall layers are described. In conclusion, robotic ventral hernia repair has gained wide acceptance with promising postoperative results. There are many different techniques and approaches available, and this paper describes the four most commonly performed procedures in a detailed step-by-step fashion.